A Global Model for Iodine Speciation in the Upper Ocean. Issue 9 (23rd September 2020) - Wadley, Martin R.; Stevens, David P.; Jickells, Tim D.; Hughes, Claire; Chance, Rosie; Hepach, Helmke; Tinel, Liselotte; Carpenter, Lucy J.
Abstract: An ocean iodine cycling model is presented, which predicts upper ocean iodine speciation. The model comprises a three‐layer advective and diffusive ocean circulation model of the upper ocean and an iodine cycling model embedded within this circulation. The two primary reservoirs of iodine are represented, iodide and iodate. Iodate is reduced to iodide in the mixed layer in association with primary production, linked by an iodine to carbon (I:C) ratio. A satisfactory model fit with observations cannot be obtained with a globally constant I:C ratio, and the best fit is obtained when the I:C ratio is dependent on sea surface temperature, increasing at low temperatures. Comparisons with observed iodide distributions show that the best model fit is obtained when oxidation of iodide back to iodate is associated with mixed layer nitrification. Sensitivity tests, where model parameters and processes are perturbed, reveal that primary productivity, mixed layer depth, oxidation, advection, surface freshwater flux, and the I:C ratio all have a role in determining surface iodide concentrations, and the timescale of iodide in the mixed layer is sufficiently long for nonlocal processes to be important. Comparisons of the modeled iodide surface field with parameterizations by other authors show good agreement in regions where observations exist but significant differences in regions without observations. This raises the question of whether the existing parameterizations are capturing the full range of processes involved in determining surface iodide and shows the urgent need for observations in regions where there are currently none. Plain Language Summary: Iodine in the ocean is important because small emissions of iodine species to the atmosphere have a significant impact on ozone and air quality. Iodine is converted between two chemical forms by phytoplankton and bacteria, but only one chemical form (iodide) results in atmospheric emissions. We have developed a model that predicts the amount of each type of iodine in the global oceans. We find that this distribution has a more complex structure than that suggested by the limited number of observations, with the ocean circulation playing an important role. The model improves our understanding of both ocean iodine cycling and the resultant impacts on ozone distribution and air quality and also shows that biological and chemical changes to the oceans due to increased atmospheric greenhouse gas concentrations are likely to result in significant changes in ocean iodine, with implications for atmospheric air quality and global elemental cycles. Key Points: We develop a model for iodine speciation and cycling in the ocean The predicted surface iodide distribution has a zonal structure not readily discernable by the limited observations to date Ocean circulation is found to have an important role in determining the spatial distribution of iodide